Comparative Analysis of CCS811 Sensor Usage in Wearable Studies for Cigarette Smoke Detection: Literature Review - Billy Maniani; Akbar Sujiwa; Primasari Cahya Wardhani; Nailul Hasan; Fajar Timur (Faraday: Journal of Fundamental Physics, Research, and Applied Science, 2025)
The CCS811 sensor is a metal oxide semiconductor (MOX)-based gas sensor that is widely used in wearable systems to monitor air quality personally, especially in detecting volatile organic compounds (VOCs) contained in cigarette smoke. This study aims to conduct a systematic review of various studies that implement the CCS811 sensor in wearable devices for cigarette smoke detection, focusing on aspects of accuracy, sensitivity, detection time, and the effect of room size. The method used is a systematic literature review of 19 scientific articles published in the last ten years. The results of the review show that the CCS811 has several advantages, such as low power consumption, compact sensor size, real-time VOC detection capability, and easy integration with the Internet of Things (IoT) system. Quantitatively, this sensor is able to detect TVOC concentrations in the range of 20–1158 ppb, with a response time of less than 20 seconds in a small space. However, limitations are still found in terms of selectivity to certain types of compounds and the lack of studies evaluating the effect of room characteristics on detection performance. This study recommends further testing in various real-world conditions as well as the application of machine learning algorithms to improve the accuracy and adaptability of the CCS811-based wearable system in effectively detecting cigarette smoke.